2019
DOI: 10.1186/s12967-019-1932-1
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Overexpression of microRNA-195-5p reduces cisplatin resistance and angiogenesis in ovarian cancer by inhibiting the PSAT1-dependent GSK3β/β-catenin signaling pathway

Abstract: Background Ovarian cancer (OC) is one of the leading causes for cancer-related deaths among women. MicroRNAs (miRs) have been proved to be vital to the development and progression of OC. Hence, the study aims to evaluate the ability of miR-195-5p affecting cisplatin (DDP) resistance and angiogenesis in OC and the underlying mechanism. Methods MiRs that could target phosphoserine aminotransferase 1 (PSAT1), a differentially expressed gene in OC, were predicted by miRNA-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 42 publications
1
37
2
Order By: Relevance
“…Upregulation of two other miRNAs (miR-152 and miR-195) in cell lines resistant to CIS and PAC could indicate their involvement in the regulation of genes associated with resistance to the first line chemotherapy of ovarian cancer. However, in contrast to our study, downregulation of miR-152 and miR-195-5p was observed in CIS-resistant ovarian cancer cell lines [51,52]. On the other hand, the upregulation of miR-195 was observed in the PAC-resistant laryngeal cancer cell line [53] and in docetaxel resistant head and neck squamous cell carcinoma [54].…”
Section: Discussioncontrasting
confidence: 99%
“…Upregulation of two other miRNAs (miR-152 and miR-195) in cell lines resistant to CIS and PAC could indicate their involvement in the regulation of genes associated with resistance to the first line chemotherapy of ovarian cancer. However, in contrast to our study, downregulation of miR-152 and miR-195-5p was observed in CIS-resistant ovarian cancer cell lines [51,52]. On the other hand, the upregulation of miR-195 was observed in the PAC-resistant laryngeal cancer cell line [53] and in docetaxel resistant head and neck squamous cell carcinoma [54].…”
Section: Discussioncontrasting
confidence: 99%
“…Upregulation of two another miRNAs (miR-152 and miR-195) in cell lines resistant to CIS and PAC could indicate their involvement in the regulation of genes associated with resistance to first line chemotherapy of ovarian cancer. However, in contrast to our study downregulation of miR-152 and miR-195-5p was observed in CIS-resistant ovarian cancer cell lines [57,58]. On the other hand, the upregulation of miR-195 has been observed in PAC-resistant laryngeal cancer cell line [59] and docetaxel resistant head and neck squamous cell carcinoma [60].…”
Section: Discussioncontrasting
confidence: 97%
“…Also, a study has presented that miR-133a-3p is participated in regulating heart development and cardiac hypertrophy [9]. A study has demonstrated that upregulation of miR-195-5p declines angiogenesis and cisplatin resistance in ovarian cancer via suppressing the phosphoserine aminotransferase 1 (PSAT1)-dependent GSK3β/β-catenin signaling pathway [10]. Another study has reported that miR-365 represses cell invasion and growth in esophageal squamous cell carcinoma (ESCC) through modulating PSAT1 [11].…”
Section: Introductionmentioning
confidence: 99%